“IT’S NOT JUST STRESS”: ANXIETY DISORDERS IN THE WORKPLACE AND THE CONTRIBUTION OF PSYCHOTHERAPY IN CASES OF LATE DIAGNOSIS (PRÁXIS EM SAÚDE, 2025)
This study investigates the underreporting of anxiety disorders in the workplace, often mistaken for occupational stress. The research, qualitative in nature and based on a literature review, uses the biopsychosocial model as its theoretical foundation. A high prevalence of anxiety is observed in professional categories exposed to emotional overload, such as health, education, and public safety. Symptoms, often normalized, are neglected by institutions that prioritize productivity over mental health care. This trivialization contributes to late diagnoses, reducing the effectiveness of interventions. Psychotherapy, especially within the cognitive-behavioral approach, has proven effective in cognitive restructuring and in preventing the chronicity of symptoms. The study reinforces the need for institutional policies that promote qualified listening, educational actions, and access to psychological services. Distinguishing adaptive stress from anxiety disorders is essential for addressing psychological suffering at work and for fostering healthier and more ethical work environments.
Keywords: Anxiety; Occupational Stress; Mental Health; Psychotherapy; Workplace